Sosio-Religious Aspects of the Sasak Community in Reading a Puspakarma Manuscript: Islamic Community Development Perspective - Rahmawati, Pudji; Muchammadun, Muchammadun; A’yun, Ariza Qurrata; Firdaus, M. Zainul (Ulumuna, 2024)
There has been intense debate over whether local practices and social engagement effectively contribute to da’wah and participatory community development. Referring to the study of a Puspakarma manuscript from Lombok, coded Gallery-50B Ciputat, the paper sheds light on the local socio-religious values that form the collective memory of Muslim Sasak communities on the island. It further argues that these values offer potential for participatory socio-religious development. The broader context of Sasak culture, as evident in the nineteenth-century Puspakarma text, provides a wider umbrella for the interpretation of elements of the manuscript’s content and message. Data analysis employs Mead’s Symbolic Interactionalism using a person-in-environment model from the perspective of Islamic Community Development. The main findings of the study are that the collective memory of ethnic Sasak Muslims recognizes the supreme being, God, and cooperative social interactions as key to community harmony, just as respect for the ancestors and nature also ensures happiness. All of these views influence community well-being. Furthermore, the author’s analysis demonstrates that each of these components found in the Sasak environment shapes the growth and development of the individual and their worldviews. This research offers fresh insight into how local development may contribute to closing the gap between cross-cultural policy and practice in Lombok and elsewhere.